Gold rush: The political economy of gold standard adoption in the Kingdom of Yugoslavia - Aleksandar R. Jevtic (The European Association for Banking and Financial History (EABH), 2020)
This paper provides a political economy perspective on gold standard adoption in the Kingdom of Yugoslavia which joined the monetary system in midst of the Great Depression in June 1931. The analysis proceeds in three stages. First, the high relative costs faced by a peripheral country like Yugoslavia for maintaining a gold standard, stemming from a fluctuating balance-of-payments and lacking institutional structures, are analysed. Against this background, the economic and political reasons why policy elites nevertheless endeavoured to adopt the gold standard are examined by looking at debates in Yugoslavia's central bank, correspondence between governmental institutions and various economic newspapers. Subsequently, the paper analyses how the convictions of policymakers were formed by looking at pressures exerted by foreign lenders such as the Bank for International Settlements and the state of economic knowledge in the country, as well as the ideological and cultural convictions of policy-makers. The third part analyses interest group pressures in bringing about the the gold standard, revealing that Serbian economic elites played a crucial role for its adoption while policy makers from Croatian regions, as well as lower layers of the Yugoslavian society opposed the monetary system and the deflationary policies it required.
Keywords: N24; N20; F55; 330; gold standard; exchange rate history; Balkan economic history